2021
DOI: 10.3390/ijms22137169
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Merkel Cell Polyomavirus Large Tumor Antigen Ubiquitin Conjugation Residue

Abstract: Merkel cell polyomavirus (MCPyV) large tumor (LT) antigen is a DNA binding protein essential for viral gene transcription and genome replication. MCPyV LT interacts with multiple E3 ligases in a phosphorylation-dependent manner, limiting its own viral replication by enhancing LT protein degradation, which is a unique mechanism for MCPyV latency. Thus, identifying LT ubiquitination sites is an important step toward understanding the biological role of these virus-host interactions that can potentially result in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Integration of the viral genome usually occurs upstream of the coding sequence for the LTA helicase domain coding sequence, resulting in a defective viral genome, unable to replicate but still able to sustain cellular proliferation by binding to the Rb protein (Houben et al, 2010 ). In a considerable number of such clones, integration occurs between the NLSm and NLSct coding sequences, generating a truncated LTA fragment whereby NLSct (and thus the bipartite NLS) is destroyed, but NLSm is preserved (Ortiz et al, 2021 ). Therefore, while full‐length MCPyV LTA can be imported to the nucleus in high levels and via multiple IMPα isoforms using a bipartite cNLS, truncated LTA fragments can still interact with the IMPα minor binding site through NLSm (Figure 8H , Figure S6 ) and be actively transported into the nucleus (Figure 8E–G ).…”
Section: Discussionmentioning
confidence: 99%
“…Integration of the viral genome usually occurs upstream of the coding sequence for the LTA helicase domain coding sequence, resulting in a defective viral genome, unable to replicate but still able to sustain cellular proliferation by binding to the Rb protein (Houben et al, 2010 ). In a considerable number of such clones, integration occurs between the NLSm and NLSct coding sequences, generating a truncated LTA fragment whereby NLSct (and thus the bipartite NLS) is destroyed, but NLSm is preserved (Ortiz et al, 2021 ). Therefore, while full‐length MCPyV LTA can be imported to the nucleus in high levels and via multiple IMPα isoforms using a bipartite cNLS, truncated LTA fragments can still interact with the IMPα minor binding site through NLSm (Figure 8H , Figure S6 ) and be actively transported into the nucleus (Figure 8E–G ).…”
Section: Discussionmentioning
confidence: 99%
“…Integration of the viral genome usually occurs upstream of the coding sequence for the LTA helicase domain, resulting in a defective viral genome unable to replicate, but still able to sustain cellular proliferation by binding to the Rb protein (57). In a considerable number of such clones, integration occurs between the NLSm and NLSct coding sequences, generating a truncated LTA fragment whereby NLSct (and thus the bipartite NLS) is destroyed, but NLSm is preserved (58). Therefore, while full-length MCPyV LTA can be imported to the nucleus in high levels and via multiple IMPa isoforms thanks to a bipartite cNLS, truncated LTA fragments can still interact with the IMPa minor binding site through NLSm (Fig.…”
Section: Conservation Of Cnlss Among All Known Pyv Ltas 95% Of Ltas F...mentioning
confidence: 99%
“…If the immunoblotting result suggested ubiquitination on the substrates, the putative ubiquitinated lysine was further mutated and analyzed by immunoblotting to evaluate whether the mutated lysine was ubiquitinated or not [30,31]. Using this kind of strategy, Ortiz et al found that the ubiquitination level of Merkel cell polyomavirus large tumor (LT) antigen was significantly reduced when K585 was substituted with R585, indicating that K585 is the ubiquitination site [32]. The conventional approaches are the most widely used ones for the detection and validation of ubiquitination for a single protein.…”
Section: Insights Into Ubiquitination At the Protein Levelmentioning
confidence: 99%